The cunning man - Butler, D. J. (David John), 1973-; Ritchey, Aaron Michael (Baen, 2020)
"It's the depths of the Depression, and a mining town in Utah is shut down. Something has awakened underground, and now a monster roams the tunnels. While contentious owners squabble, poor worker families go hungry. Along comes Hiram Woolley. Hiram is a man with mystical abilities derived from the commonsense application of Scots-Irish folk wisdom and German braucher magic. Hiram must confront the monster below, as well as a family of mine owners who would rather watch children go hungry than compromise with each other. The job will take a man who has known sorrow. A man who has known war. A man of wisdom. A man of magic. A Cunning Man."--Page 4 of cover